An Islamic Values-Based Evaluation of the Shortcomings in the Smart Indonesia Scholarship Program - Saputri, Dewi Puput; Nurhayati, Agustina; Mu’in, Fathul (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
The Indonesia Smart Program (PIP) is a strategic governmental initiative designed to enhance access to higher education for students from economically disadvantaged backgrounds. Despite its intended benefits, the program’s implementation within faith-based higher education institutions—such as Raden Intan State Islamic University (UIN) in Lampung—continues to encounter structural and ethical challenges, particularly among scholarship recipients residing in Ma’had al-Jami’ah (Islamic boarding schools). This study aims to examine the implementation of Minister of Education and Culture Regulation No. 10 of 2020, identify both supporting and inhibiting factors, and evaluate the policy through the lens of Islamic public law (Fiqh Siyasah Tanfidziyah). Employing a descriptive qualitative method and a normative-sociological approach, the study finds that while the PIP has contributed positively to educational participation, it still faces issues related to data validation, delays in fund disbursement, and misallocation of resources. From the perspective of Islamic jurisprudence, the findings underscore the necessity of upholding the principles of trustworthiness, justice, and transparency in public policy implementation. Ongoing evaluation and reform are essential to align the program with Islamic ethical values and to promote more equitable educational outcomes.